2017
DOI: 10.1007/s41061-017-0131-x
|View full text |Cite
|
Sign up to set email alerts
|

Polymer–Nucleic Acid Interactions

Abstract: Gene therapy is an important therapeutic strategy in the treatment of a wide range of genetic disorders. Polymers forming stable complexes with nucleic acids (NAs) are non-viral gene carriers. The self-assembly of polymers and nucleic acids is typically a complex process that involves many types of interaction at different scales. Electrostatic interaction, hydrophobic interaction, and hydrogen bonds are three important and prevalent interactions in the polymer/nucleic acid system. Electrostatic interactions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 110 publications
2
20
0
Order By: Relevance
“…Increasing the DNA length and N/P ratio results in disappearance of the negatively charged complex. Nucleic acids can interact with amines by the means of ionic interactions through phosphate groups or by hydrogen bonds through nucleobases [40,41] and references in this review. The latter mechanism suggests that the negatively charged free phosphate groups compensates the positive charge of the free amine units.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing the DNA length and N/P ratio results in disappearance of the negatively charged complex. Nucleic acids can interact with amines by the means of ionic interactions through phosphate groups or by hydrogen bonds through nucleobases [40,41] and references in this review. The latter mechanism suggests that the negatively charged free phosphate groups compensates the positive charge of the free amine units.…”
Section: Resultsmentioning
confidence: 99%
“…Their fundamental building blocks are planar tetrads composed of four guanine nucleobases (G‐tetrad) that engage in Hoogsteen‐type base pairing (Scheme A) . Typically, two to four of these tetrads are stacked on top of each other to form the structural motif, though larger assemblies have been reported as well (Scheme B) . G‐quadruplex folding requires monovalent cations, such as K + or Na + , because the positive charge stabilizes the partially negatively charged O6 atoms of the guanine bases .…”
Section: Introductionmentioning
confidence: 99%
“…20 Indeed, it is known that a strong electrostatic interaction exists between the phosphate groups of DNA and the amino groups of spermine, as well as hydrophobic and hydrogen bonds. 21 Nanoparticles stability and nucleic acid protection are important parameters for efficient nucleic acid delivery. 22 Release profiles of nanoparticles made with GOAS-pEGFP-p53 incubated in PBS showed that these structures were able to release DNA constantly over 30 days.…”
Section: Discussionmentioning
confidence: 99%